Uncountably many 2-generated just-infinite branch pro-2 groups - Benli, M.G.; Grigorchuk, R. (Algebra and Discrete Mathematics, 2015)
The aim of this note is to prove that there are 2ℵ0 non-isomorphic 2 generated just-infinite branch pro-2 groups.